2021
DOI: 10.2147/ndt.s336077
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Retinal Nerve Fiber Layer Thickness, Vascular Endothelial Growth Factor, and Cognitive Impairment in Patients with Schizophrenia

Abstract: Background Studies have suggested retinal nerve fiber layer (RNFL) involvement in the pathogenesis of schizophrenia. Additionally, research has shown that vascular endothelial growth factor (VEGF) potentially contributes to the pathophysiology of psychiatric disorders. Therefore, this study aimed to investigate VEGF, RNFL, and correlations with cognitive impairments in schizophrenia patients. Methods Patients with schizophrenia (n = 138) were compared to healthy control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In contrast, not found any correlation between language, attention, delayed memory, and RNFL (31). The other study of the same group reported a significant correlation between RNFL thickness thinning and lower scores on the Stroop Color Word reading test (32). Finally, a recent study examined the correlations between executive functioning, attention, memory/learning and OCT results.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In contrast, not found any correlation between language, attention, delayed memory, and RNFL (31). The other study of the same group reported a significant correlation between RNFL thickness thinning and lower scores on the Stroop Color Word reading test (32). Finally, a recent study examined the correlations between executive functioning, attention, memory/learning and OCT results.…”
Section: Discussionmentioning
confidence: 92%
“…The authors noted that better cognitive performance was related to a thicker RNFL in only young individuals, but this association diminished in older age groups (30). In schizophrenia, a few studies assessed the cognitive correlations of retinal findings (17,31,32). One study found that lower scores of immediate memory and visuospatial functions of the RBANS (Repeatable Battery for the Assessment of Neuropsychological Status) were correlated with a decline in RNFL thickness.…”
Section: Discussionmentioning
confidence: 99%
“…In subgroup analysis, only drug-naïve patients displayed decreased NGF (SMD, −2.16; 95% CI, −4.02--0.31; p = 0.022; Table 2), while no significant differences were detected based on other treatment statuses (i.e., unmedicated or medicated), illness stages (i.e., FEP and non-FEP) or sample origins (i.e., plasma and serum). Blood vascular endothelial growth factor (VEGF) level also did not differ between all patients and controls (SMD, 0.11; 95% CI, −0.17-0.39; p = 0.447) (88,90,95,(110)(111)(112)(113)(114)(115)(116)(117). It was decreased in one study with drug-naïve patients (SMD, −0.77; 95% CI, −1.23--0.31; p = 0.001) (111), but not with other treatment statuses, illness stages, or sample origins.…”
Section: Angiogenesismentioning
confidence: 98%